2016
DOI: 10.1002/aelm.201500352
|View full text |Cite
|
Sign up to set email alerts
|

An Energy‐Efficient, BiFeO3‐Coated Capacitive Switch with Integrated Memory and Demodulation Functions

Abstract: A capacitive switching behavior is observed in a Si3N4/p‐Si‐based metal–insulator–semiconductor (MIS) structure due to the electron tunneling at the Si3N4/p‐Si interface. A BiFeO3 (BFO) layer is deposited on Si3N4/p‐Si by pulsed laser deposition technique to obtain the memcapacitive effect as the distribution of positive charges in the Si3N4 layer can be stabilized by the polarization charge of the ferroelectric BFO coating layer. The capacitive switching behavior of the Al/BFO/Si3N4/p‐Si/Au MIS structure is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
12
1
Order By: Relevance
“…The positive fixed and mobile charge defects in the insulating Si 3 N 4 layer cause a shift of the flat band voltage to larger negative bias. The mobility of the mobile defects in Si 3 N 4 depends on the PLD growth temperature during deposition of the n-type semiconductor on the insulator Si 3 N 4 , namely 550 °C for the deposition of ZnO in this work and 380 °C for the deposition of BiFeO 3 in a previous work 22 . It has been reported that the threshold temperature for the formation of defects in Si 3 N 4 lies at circa 500 °C 23 .…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The positive fixed and mobile charge defects in the insulating Si 3 N 4 layer cause a shift of the flat band voltage to larger negative bias. The mobility of the mobile defects in Si 3 N 4 depends on the PLD growth temperature during deposition of the n-type semiconductor on the insulator Si 3 N 4 , namely 550 °C for the deposition of ZnO in this work and 380 °C for the deposition of BiFeO 3 in a previous work 22 . It has been reported that the threshold temperature for the formation of defects in Si 3 N 4 lies at circa 500 °C 23 .…”
Section: Resultsmentioning
confidence: 68%
“…With increase in oxygen vacancies at the surface, bound magnetic polaron formed with oxygen vacancy as nucleus can overlap and provide ferromagnetic behaviour at room temperature 45 Davies et al 46 and Kaspar et al 7 suggest that ferromagnetic features from bound magnetic polaron can be used in developing magnetic sensors, non-volatile memories in spintronics devices which are potentially expected to be energy-efficient devices. Application of BFO coated Si 3 N 4 MIS structure as a photocapacitive detector has been studied by You et al 22 . Because ZnO is transparent and because the ZnO coated Si 3 N 4 MIS structure shows similar capacitance behaviour as the BFO coated Si 3 N 4 MIS structure, the ZnO coated Si 3 N 4 MIS structure is expected to reveal similar photocapacitive functionality as the BFO coated Si 3 N 4 MIS structure to detect intensity and color of visible light by impedance measurements.…”
Section: Discussionmentioning
confidence: 99%
“…39 Thus the memductance state can be controlled either by optical or electrical pulses or by combinations of both, which allows the integration with photodetectors as sensory neurons. The conductance control is further sensitive to the wavelength of incoming light 51 , which was also demonstrated with other memristors 52 and memcapacitors 53 and enables encoding information in the wavelength. For the present device, the light sensitivity leads to varying learning processes in the dark and under illumination, which is the key advantage compared to other memristor realization with large on/off ratios of up to 10 12 , 54 low switching times in the sub-nanosecond range 55 or high endurance (10 12 cycles).…”
Section: Discussionmentioning
confidence: 96%
“…To date, a few studies on memcapacitive switching have been observed in MIS (metal‐insulator‐semiconductor) structure with a dielectric layer through the charge trapping effect or ion migration into/out of dielectric by varying an external voltage. [ 9–15 ] In particular, memcapacitive and memristive switching usually coexist in such MIS structures, [ 15 ] most of these are unsuitable for future design and optimization as memcapacitive devices.…”
Section: Introductionmentioning
confidence: 99%